Searching For Love In Jean Marc Vallee's The Young Victoria Movie (2009): An Existentialist Approach - Hasanah, Endah (2012)
This study is about search for love in The Young Victoria movie (2009). This objective of the study is to apply the Existentialist approach to analyze search for love in The Young Victoria movie. The technique of analyzing data is descriptive and uses method of documentation. The writer uses Sartre's major point of Existentialism to answer the problem of the study. The type of study is descriptive qualitative research whose data are taken from two data sources: primary and secondary. The study comes to the following conclusion. Firstly, based on the structural analysis of each elements, it shows that the character and characterization, plot, setting, point of view, theme, casting, mise-en-scene, cinematography, sound, and editing are related one another. Second, based on the existentialist analysis, human has different existences which based on different being, choice, anxiety and etc. Human has a freedom to choose and takes responsibility for his choice. The responsibility makes human feel anxiety. Jean Marc Valle shows the struggle from Victoria in searching her love. The Director tries to show the moral value, that human must do some efforts to get his love without sacrifices their obligation. It means that everything must be balanced and human must takes responsibility not only for himself but also for the whole humanity.